Economic arguments in migrant health policymaking: proposing a research agenda - Gottlieb, Nora; Trummer, Ursula; Davidovitch, Nadav; Krasnik, Allan; Juárez, Sol P.; Rostila, Mikael; Biddle, Louise; Bozorgmehr, Kayvan (Globalization and health, 2020)
Welfare states around the world restrict access to public healthcare for some migrant groups. Formal restrictions on migrants’ healthcare access are often justified with economic arguments; for example, as a means to prevent excess costs and safeguard scarce resources. However, existing studies on the economics of migrant health policies suggest that restrictive policies increase rather than decrease costs. This evidence has largely been ignored in migration debates. Amplifying the relationship between welfare state transformations and the production of inequalities, the Covid-19 pandemic may fuel exclusionary rhetoric and politics; or it may serve as an impetus to reconsider the costs that one group’s exclusion from health can entail for all members of society.